Kajian Yuridis Marrital Rape dalam Perspektif Sistem Hukum Nasional Indonesia dan Hukum Islam - Dewi Silva Sari (Jurnal Indonesia Sosial Sains, 2022)
The aims of this study are as follows : First, to find out marrital rape in the perspective of the Indonesiain National legal system, Second, To study and find out about marritale rape from the perspective of islamic law. The type of research that will be used in this legal research is normative/doctrinal legal research. The object of this research is the law which is conceptualized as what is written in legislation. The legal materials used are primary legal materials, secondary legal materials, and tertiary materials. While the approach used is a statutory approach. The results of this discussion include at the positive legal level marrital rape is regulated in varoius laws and regulations including the law on the elimination of dmestic violince oe the so-called PKDRT Law and is also still in the discussion stage on the Draft Lae on the elimination of sexual violence. Or reffered to as the PKS bill. In the criminal code, it is clearly regulated regardingthe crime of rape, but the regulations do not refer to rape in the household. In Islamic law the matter of marrital rape is not clearly regulated, but the word of God in Q.S Al baqarah (2): (187 ) can be a reference for all Muslims thet the position between husband and wife is equal. So, Far Islamic Law has not been able to answer cleraly and unequivocally regarding the problems of marritale rape that still continue to occur, evevn thouh it has been regulated in such a way In Indonesian Positive Law.